Electrochemical Determination of Caffeic Acid in Wine Samples Using Reduced Graphene Oxide/Polydopamine Composite. Issue 14 (23rd November 2016) - Thangavelu, Kokulnathan; Palanisamy, Selvakumar; Chen, Shen-Ming; Velusamy, Vijayalakshmi; Chen, Tse-Wei; Ramaraj, Sayee Kannan
Abstract : We report a novel caffeic acid (CA) electrochemical sensor using reduced graphene oxide and polydopamine composite modified glassy carbon electrode. Electrochemical method was applied on graphene oxide (GO) and PDA composite modified electrode for the preparation of RGO@PDA composite. The RGO@PDA composite was used as an electrocatalyst for the oxidation of CA. Cyclic voltammetry (CV) was used to investigate the electrochemical behavior of different modified electrodes toward oxidation of CA and the CV results show that RGO@PDA composite has high electrocatalytic activity to CA than other modified electrodes. Optimization studies such as effect of catalyst loading and pH are investigated and discussed. Differential pulse voltammetry was used for determination of CA, and shows that the response of CA was linear over the concentration ranging from 5.0 nM to 450.55 μM with the low detection limit of 1.2 nM. The selectivity of the sensor was elevated in the presence of potentially active interfering species, and the results reveal that the composite modified electrode has acceptable selectivity in the presence of interfering species. The practical applicability of the composite was evaluated in wine samples and the obtained recovery of CA in wine samples authenticates its potential for practical applications.